Heterochronic evolution explains novel body shape in a Triassic coelacanth from Switzerland - Lionel Cavin (Nature Portfolio, 2017)
Abstract A bizarre latimeriid coelacanth fish from the Middle Triassic of Switzerland shows skeletal features deviating from the uniform anatomy of coelacanths. The new form is closely related to a modern-looking coelacanth found in the same locality and differences between both are attributed to heterochronic evolution. Most of the modified osteological structures in the new coelacanth have their developmental origin in the skull/trunk interface region in the embryo. Change in the expression of developmental patterning genes, specifically the Pax1/9 genes, may explain a rapid evolution at the origin of the new coelacanth. This species broadens the morphological disparity range within the lineage of these ‘living fossils’ and exemplifies a case of rapid heterochronic evolution likely trigged by minor changes in gene expression.